TECHNICAL EFFICIENCY ANALYSIS OF ONION FARMING ON UPSUS APBN-P 2017 PROGRAM USING STOCHASTIC FRONTIER ANALYSIS APPROACH (CASE STUDY IN GONDANG SUB-DISTRICT, NGANJUK REGENCY) - Anugrah Rizki Pratama (Socio-Economics/Agribusiness Department, 2018)
These study aims to the analyze factors that affect the production of onion farming, to analyze the level of technical efficiency of onion farming, and to analyze the factors that affect the inefficiency onion farming in UPSUS APBN-P 2017 Program. This research uses Stochastic Frontier production function analysis method with Maximum Likelihood Estimation (MLE) approach which aims to analyze production factors that influence on onion production. The second analytical method is using tobit regression that aims to determine what factors affect the technical inefficiency in onion farming in Gondang Sub-district.The result of this research is known that the significant effect on onion farming production inGondang Sub-district are seed, urea fertilizer, KCl fertilizer, ZA fertilizer, and labor. The average value of efficiency achieved is equal to 0.71. The total of 52 farmers are technically efficient and as many as 38 farmers are technically inefficient. In the result of tobit regression analysis, it is known that the factors that significantly influence the technical inefficiency of onion farming in Gondang sub-district are age, farming experience, training participation, and program officer control.